A dual-control strategy based on electrode material and electrolyte optimization to construct an asymmetric supercapacitor with high energy density. (14th May 2022) - Chu, Xianyu; Meng, Fanling; Zhang, Wei; Yang, He; Zou, Xu; Molin, Sebastian; Jasinski, Piotr; Sun, Xiangcheng; Zheng, Weitao
Abstract: Metal-organic frames (MOFs) are regarded as excellent candidates for supercapacitors that have attracted much attention because of their diversity, adjustability and porosity. However, both poor structural stability in aqueous alkaline electrolytes and the low electrical conductivity of MOF materials constrain their practical implementation in supercapacitors. In this study, bimetallic CoNi-MOF were synthesized to enhance the electrical conductivity and electrochemical activity of nickel-based MOF, as well as the electrochemical performance of the CoNi-MOF in multiple alkaline electrolytes was investigated. The CoNi-MOF/active carbon device, as-fabricated with a 1 M KOH electrolyte, possesses a high energy density of 35 W h kg −1 with a power density of 1450 W kg −1, exhibiting outstanding cycling stability of 95% over 10, 000 cycles. The design of MOF-based electrode materials and the optimization selection of electrolytes pave the way for constructing high-performance supercapacitors.